2009
DOI: 10.1364/oe.17.019476
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nano lithography
 with a high scan speed contact probe

Abstract: We demonstrate plasmonic lithography with an optical contact probe to achieve high speed patterning without external gap distance control between the probe and the photoresist. The bottom surface of the probe is covered with a 10 nm thickness silica glass film for the gap distance control and coated with self-assembled monolayer (SAM) to reduce friction between the probe and the photoresist. We achieve a patterning resolution of ~50 nm and a patterning speed of ~10 mm/s. We obtain the quality of line patternin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…Prospective applications of such nano-SILs include near-field focusing and imaging 12 , optical data storage 26 , and maskless direct-write lithography 27 . Furthermore, the introduction of plasmonic structures on the bottom of the SIL could further improve performance and resolution 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Prospective applications of such nano-SILs include near-field focusing and imaging 12 , optical data storage 26 , and maskless direct-write lithography 27 . Furthermore, the introduction of plasmonic structures on the bottom of the SIL could further improve performance and resolution 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al reported a plasmonic lithography technique with bowtie-shaped contact probes [98]. As illustrated in Fig.…”
Section: Spps Direct Writing Nanolithographymentioning
confidence: 99%
“…Various maskless lithography techniques have been developed, such as plasmonic lithography [15], zone plate array lithography (ZPAL) [16,17], and nanoimprint lithography [18]. Among the various maskless lithography techniques, researchers have developed ML systems based on DMDs and subsequent applications since Chan et al had proposed a DMD-based ML system [8,9].…”
Section: Introductionmentioning
confidence: 99%